Komunikasi Interpersonal Pengungkapan Diri (Self-Disclosure) Penggunaan Second account di Instagram (Studi Pada Mahasiswa Ilmu Komunikasi Angkatan 2020 Universitas Islam Balitar Blitar): Studi Pada Mahasiswa Ilmu Komunikasi Angkatan 2020 Universitas Islam Balitar Blitar - Alfina; Meifilina, Andiwi; Kusumawijayanti, Anita Reta (Universitas Islam Balitar, 2024)
This study aims to determine the form and impact of interpersonal communication, self-disclosure, the use of second account on Instagram, a study on Communication Science Students Class of 2020 at Balitar Islamic University Blitar. This research uses qualitative descriptive methods and uses purposive sampling techniques in collecting informants. Data collection using techniques: Interview, Observation, Documentation. The results of this study are forms of interpersonal communication self-disclosure (self-disclosure) on second Instagram accounts, Communication Science Students Class of 2020 photos, videos and meaningful words (quotes) on Instagram stories and feeds. The positive impact encountered, students can get to know themselves, the effectiveness of communication between informants and second account followers, avoid stress, feelings of relief, the emergence of emotional feelings such as empathy and mutual support, and maintain privacy. The negative impact obtained by informants is unpleasant comments, a sense of concern about the perspective of others, and dependence on second account.